Letter of Contract in Electronic Commerce (e-Commerce) Based on Civil Law - Ruslin Ruslin (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Internet Development has created the new form atmosphere named virtual world. The existence of virtual media has developed every personality is determined to relate limitless bound communication one another. The improvement caused to social aspect where it may change human relationship. The change has allowed people or company to perform any business transactions especially in commerce. It has explicitly affected to business sectors. Trading Officials E-Commerce Issuance is not as usual in common, but the issuance is commenced instead of obvious between both officials, but it may be adjusted in electronic way. Keywords: electronic commerce; letter of contract